Sharia Financing Online Education: Mudhorobah, Musyarokah and Murobahah Financing - Ni'Mah, Heni Sholikhatun; Nestovani, Eldora Christabel; Nugraha, Yoga Satria; Sayekti, Dania Tutra Eka (Journal of Islamic Economy and Community Engagement, 2023)
The majority of Indonesia's population is Muslim, which means that it has great potential to become a center for the development of Islamic finance, including Islamic banking. However, the results of an OJK survey found that only 21.48% of Indonesia's population is classified as well-intentioned. This shows the low level of financial literacy of the Indonesian people. It can be said that the development of Islamic finance in Indonesia which is still relatively low is due to the lack of financial literacy of the people. Therefore, this service aims to provide additional insight regarding the introduction of Islamic banking, products produced by Islamic banking, the benefits of using Islamic banking. It is hoped that with this discussion of information, public understanding regarding Islamic banking will increase. To carry out these activities, our team disseminates understanding of Islamic banking by providing information and opening discussions through posts we make on Instagram. In the future, it is hoped that the public will be able to pass on this information to a wider audience and be able to use Islamic banking wisely.